Centra pro závislé na tabáku v České republice v roce 2012: přehled, ekonomika - Králíková, Eva; Kmeťová, Alexandra; Felbrová, Vladislava; Kulovaná, Stanislava; Rameš, Jiří; Stěpánková, Lenka; Zvolská, Kamila; Skoupá, Jana (Casopis lekaru ceskych, 2014)
BACKGROUND: Since 2005, in the Czech Republic the Centres for Tobacco-Dependent are being established at hospitals. METHODS: Evaluation of the activity of these 37 centres in 2012, economic analysis of treatment costs and assessment of the cost of life year gained (LYG). RESULTS: Most of the centres (26 of 37) are based at pulmonary clinics with opening hours for smokers: on average 7 hours/week. Treatment codes 25501 and 25503 are used at 28 centres. Entry visit usually takes on average 61 minutes, follow-up visits 22 minutes. Nicotine replacement therapy and varenicline are indicated in all centres, but only 14 centres use bupropion. Virtually all centres use links to other clinical disciplines, about 10.5 % of patients are sent to other departments. The most common barriers for wider activity are insufficient salaries and staffing. In 2012, the Centre for Tobacco-Dependent at the 3rd Medical Department, 1st Faculty of Medicine, Charles University in Prague and the General University Hospital treated 430 patients for the price of 3792 CZK per treated patient ( 150 Euro), respectively, with 38 % success rate for the price of 10,003 CZK per abstinent patient ( 400 Euro), or for 1,334 CZK per LYG ( 50 Euro/LYG). CONCLUSION: In the future it would be good to improve working conditions in centres and to take advantage of their potential for the indispensable, effective and highly cost-effective treatment.
Keywords: prostředky pro ukončení závislosti na tabáku; Smoking Cessation; analýza nákladů a výnosů; Cost-Benefit Analysis; Humans; Tobacco Use Cessation Devices; Substance Abuse Treatment Centers; Tobacco Use Disorder; Czech Republic; odvykání kouření; poruchy vyvolané užíváním tabáku; lidé; centra pro terapii drogových závislostí; Česká republika